Food borne infection by a Norwalk like virus (small round structured virus). Issue 7 (July 1984) - Riordan, T; Craske, J; Roberts, J L; Curry, A
Abstract : Two outbreaks of gastrointestinal illness with identical symptoms occurred in parties attending banquets on consecutive evenings at a large hotel. The illness was typical of epidemic winter vomiting disease. Small round structured viruses resembling those seen in the Norwalk Ohio outbreak were identified by electron microscopy in stools of victims from one episode. One food handler was found to be excreting the virus, and there was evidence of a poor standard of hygiene in the kitchen. A food history analysis showed the illness to be significantly associated with eating cold cooked ham.